The discovery of igneous xenoliths in the Upper Zone of the Bushveld Igneous Complex and its implications on the model of emplacement of Upper Zone magmas - Roberts, R.J. (James) (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 2023.